2003
DOI: 10.1243/095441003763031815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the turning angle on the flow and performance characteristics of long S-shaped circular diffusers

Abstract: The effect of the turning angle on the¯ow and performance characteristics of long Sshaped circular diffusers (length±inlet diameter ratio, L=D iˆ1 1:4) having an area ratio of 1.9 and centre-line length of 600 mm has been established. The experiments are carried out for three S-shaped circular diffusers having angles of turn of 158/158, 22.58/22.58 and 308/308. Velocity, static pressure and total pressure distributions at different planes along the length of the diffusers are measured using a ®ve-hole impact p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…The static pressure coefficient is defined by Eq. (12) where p in and p in are the mass-weighted average static and total pressure at inlet, respectively, and p represents the static pressure at a particular location along the S-shaped duct walls. Figure 3 is an illustration of a comparison of predicted and existing experimental results [3].…”
Section: Numerical Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The static pressure coefficient is defined by Eq. (12) where p in and p in are the mass-weighted average static and total pressure at inlet, respectively, and p represents the static pressure at a particular location along the S-shaped duct walls. Figure 3 is an illustration of a comparison of predicted and existing experimental results [3].…”
Section: Numerical Methods Validationmentioning
confidence: 99%
“…Due to the curvature of the S-shaped duct, the streamwise and radial direction encounter a pressure gradient and the presence of this pressure gradient significantly modifies the boundary layer development within the S-shaped duct. This is the reason why a vast majority of researchers [6][7][8][9][10][11][12][13][14] have given paramount importance to the influence of wall curvature on the performance of the S-shaped duct in their studies. Space and weight optimization in the aviation industry dictate that the transition duct must be as shorter as possible without the occurrence of flow separation.…”
Section: Introductionmentioning
confidence: 99%
“…Anand 4 [2001] studied on the effect of the turning angle on the flow and performance characteristics of long S-shaped circular diffusers. He established the effect of the turning angle on the flow and performance characteristics of long S-shaped circular diffusers (length-inlet diameter ratio, L/D i = 11.4 having an area ratio of 1.9 and centre-line length of 600 mm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to this curvature, a pressure gradient along the streamwise as well as radial direction is found, and therefore boundary layer development within the duct will significantly get modified. This is the reason why a huge majority of researchers [8][9][10][11][12][13][14][15][16] have given paramount importance to the influence of wall curvature on the performance of the S-shaped duct in their studies. Apart from these, some researchers investigated Influence of wakes coming out from upstream compressor and found that with upstream compressor stage, the proclivity of flow to be separated on the inner wall had significantly reduced because the wakes induced by the compressor blades reenergize the inner wall boundary layer and eventually reduced the pressure gradient.…”
Section: Introductionmentioning
confidence: 99%